Scheduling model of construction activity with time couplings - Hejducki, Zdzisław (Journal of Civil Engineering and Management, 2003)
The algorithm of construction work graphic schedule which takes into account the proper sequencing problem has been presented. The algorithm is described step by step, ie the construction work organisation methods with zero couplings between realisation means. The calculation process of “Limit Possible Minimum” (LPM) taking into account technical and organisation limits is also shown. The second part of the paper includes a practical example which presents the method and the optimisation algorithm for the work organisation method with zero couplings among realisation means. First Published Online: 26 Jul 2012